2013
DOI: 10.1063/1.4812219
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced resistive switching effect in Ag nanoparticle embedded BaTiO3 thin films

Abstract: Ag nanoparticle (NP) embedded BaTiO 3 (BTO) thin films on SrRuO 3 -coated SrTiO 3 (STO) substrates are prepared by the integrated nanocluster beam deposition and laser-molecular beam epitaxy. Enhanced resistive switching, up to an ON/OFF ration of 10 4 , has been achieved at low switching voltage (less than 1 V) without a forming voltage. These characteristics make such nanocomposite film very promising for application of low voltage non-volatile random access memory. The enhanced resistive switching effect ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…Composite ferromagnets for example, can be used in magnetic field sensors, due to a high sensitivity of their resistance to a magnetic field change. Granular ferroelectrics -subject of this work -are useful in memory 11,12 and capacitor 13,14 applications because of their hysteresic behavior and their high dielectric permittivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite ferromagnets for example, can be used in magnetic field sensors, due to a high sensitivity of their resistance to a magnetic field change. Granular ferroelectrics -subject of this work -are useful in memory 11,12 and capacitor 13,14 applications because of their hysteresic behavior and their high dielectric permittivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transport properties of composite ferroelectric materials were studied experimentally 12 . It was shown that GFEs exhibit two important features: i) switching between different resistive states and ii) a current voltage hysteresis.…”
mentioning
confidence: 99%
“…These results suggest that the nitrogen doping method in WO x thin film produces new species of WN and W x (O, N) in the WO x :N thin film, improving the RS properties in WO x :N thin film [18]. It has been reported that metal nanoclusters embedded in insulators can generate a locally focused electric field, which assists oxygen vacancies to be locally aligned to form stable CFs in insulators [19,20]. Similarly, in this work, it is thought that metallic WN nanoclusters generated by nitrogen doping in WO x :N thin films might enhance the electric field for alignments of the oxygen vacancies between WN nanoclusters, resulting in the improved RS properties in WO x :N thin film.…”
Section: Fig 1(a) and (B)mentioning
confidence: 94%
“…[1][2][3][4][5] However, despite their good retention and endurance properties, two problems need to be resolved before taking into consideration device applications. One of the issues is to develop a reliable and compatible process for facile and low-cost fabrication, 1 the other is about improving memory switching parameters.…”
Section: Introductionmentioning
confidence: 99%